Pemberdayaan Perempuan melalui Hilirisasi Produk Bawang Goreng di Desa Bigo Selatan - Pobela, Elva; Muharto; Bansaleng, Yessikah (Yayasan Rahmatan Fidunya Wal Akhirah, 2026)
The Community Service Program (PM-BEM) in South Bigo Village, Kaidipang District, North Bolaang Mongondow Regency aims to increase women's economic independence through the downstream processing of local agricultural products, particularly shallots, into high-value fried onions. This activity focuses on empowering the Mososengga Dasawisma Group through technical training, managerial mentoring, and the application of appropriate technology. The implementation method is participatory, including socialization, production training, the application of chopping and spinner tools, business mentoring, and sustainability planning. The results of the activity show an increase in production capacity, work time efficiency, and product quality, with an average of 7-10 kg of fried onions per week. In addition, group members have been able to implement simple financial records, brand the product